Now museum, now you don't - Miedoso, Andres (Miedoso, Andres. Desmond Cole ghost patrol, 2019)
"Museums are great places to see really old stuff. The Kersville Museum has old paintings, old statues, and even old mummies that come with old curses. Sounds like a perfectly safe place to visit for family fun. Until the mummies start to disappear!"--Page [4] of cover.